Sporulation in mycobacteria: New paradigm or scientific fraud? (Veterinary Science, 2017)
This article shows the need to maintainrigueur in applying the scientific methodthrough the analysis of two publications onthe topic of mycobacterium sporulation. It alsoshows the importance of the evaluators andeditors of scientific magazines real work toavoid the fraud and confusion in establishinga new paradigm.
Keywords: fraud; new paradigm; scientific publications.